Descriptive Analysis of the Long Head of the Biceps Abnormalities in Distal Isolated Supraspinatus Tears Based on Video Records: A Study From the SFA Biceps Study Group Using the "Biceps Box" Concept - Johannes Barth MD; Julien Berhouet MD, PhD; David Gallinet MD; Maxime Antoni MD; Franck Dordain MD; Nicolas Bonnevialle MD, PhD; Jacques Guery MD; François Gadea MD; Adrien Jacquot MD; Christophe Charousset MD (SAGE Publishing, 2024)
Background: Considering the long head of biceps (LHB) management, important cultural differences exist among the surgeons around the world, especially when repairing small isolated distal supraspinatus tears under arthroscopy. In the perspective of an international survey to analyze our practice regarding biceps management in small rotator cuff tears, the aim is to collect all the possible LHB abnormalities according to literature review, before considering that the LHB could be normal or pathologic. Indications: The SFA (Société Francophone d'Arthroscopie) behind its research biceps group summarized these abnormalities in a description analysis called the "biceps box" concept, which was validated with a strong inter-rater reliability. The aim is to present the description analysis using a common language with short video records for each abnormality described to reproduce "intraoperatively" the different possible scenarios the surgeon has to encounter during arthroscopic evaluation. Technique Description: The description of the "biceps box" concept classifies lesions of the LHB, with so-called intrinsic lesions, for which the LHB should be considered pathological: partial rupture or delamination, fissuring, lateral or medial instability or subluxation, hypertrophy with an hourglass figure; and so-called extrinsic lesions, for which the LHB should be considered healthy: damage to the pulley without bicipital instability, exposure of the articular portion of the biceps by rupture of the supraspinatus tendon, inflammation of the superficial surface of the tendon, presence of type 1 or 2 superior labral anterior to posterior (SLAP) lesions, or a chondral print. Results: We present the 10 possible scenarios with video records according to our description analysis. Discussion/Conclusion: The LHB could be considered as a pain generator in certain situations which are still not completely clear. The indication of biceps tenotomy or tenodesis depends on the interpretation of the surgeon of these abnormalities as a pathologic or a normal condition. The next step is to use these videos in an international survey to assess cultural differences regarding the management and eventually find a consensus regarding treatment options for each abnormality. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.